Relationship between tobacco smoking and hematological indices among Sudanese smokers - Izzut Awad Ahmed; Mahmood Abdalmonem Mohammed; Hussam Mohammed Hassan; Ibrahim Abdelrhim Ali (BMC, 2024)
Abstract Background Tobacco Smoking is one of the leading causes of preventable morbidity and mortality in the world. It is well documented that tobacco smoking is risk factor for many diseases like: cancers, chronic respiratory and cardiovascular diseases, and the effects of tobacco smoking on hematological indices gets a little attention: the data is mostly inconsistent regarding the differential of WBCs, a conflicting studies described the effect of smoking on hemoglobin descriptive parameters and a regular monitoring of platelets count in smokers was advised. Objectives The study aimed to evaluate the relationship between tobacco smoking and hematological parameters among Sudanese healthy Smokers at Bahri Town. Methods This was a cross sectional study conducted during 2022 in Bahri town, Khartoum state. A total of 120 male subjects participated in this study. Of them, 60 healthy non-smokers participants (Control), and 60 age matched smokers who were smoking tobacco for a minimum of 1 year. Smokers group was divided into three major sub-groups with each group contains 20 subjects: Cigarettes smokers (CS), Water pipes (Shisha) smokers (WP) and both Cigarettes and water pipes (shisha) smokers (CSWP). Data was collected through questionnaire interviews and laboratory investigation. A sample of Five ml venous blood was taken for Complete blood count testing using Urite 3000 plus semi-automated hematology analyzer. Data were analyzed using SPSS version 25. Assocation between the variables were estimated and p value ≤ 0.05 was considered statistically significant. Results Smokers had significantly higher RBCs count (p = 0.017), Hb level (p < 0.001), WBCs count (p = .017), Neutrophils (p < 0.001), MCH (p = 0.029), MCHC (p < 0.001), RDW (p < 0.001), and PDW (p < 0.001) compared to the non-smokers. In contrast, non-smokers had higher MPV (p < 0.001) and MCV (p < 0.001) levels than smokers. Between the non-smokers and different subtypes of the smokers (CS, WP & CSWP), there were significant differences between the subgroups for all hematological parameters except for PLTs and lymphocytes count. CS had lower levels of MCV (p < 0.001), MCHC (p < 0.001), HCT (p = 0.036), and RDW (p < 0.001) compared to the non-smokers, while both cigarette and shisha smokers had the higher levels of neutrophils count (p < 0.001) and PDW (p < 0.001) compared to the non-smokers. Conclusion Smoking affects hematological parameters; smokers had significantly higher RBCs count, Hb level, WBCs count, Neutrophils, MCH, MCHC, RDW and PDW compared to the non-smoker group. WP smoking caused higher levels of RBCs, Hb, neutrophils, MCH and MCHC. PDW was high in smokers' sub-groups compared to control group, while MPV was lower despite insignificant change In PLTs count.